2016
DOI: 10.1021/acs.joc.6b00553
|View full text |Cite
|
Sign up to set email alerts
|

Three-Step Synthesis of Fluoranthenes through Pd-Catalyzed Inter- and Intramolecular C–H Arylation

Abstract: A three-step synthetic method for the preparation of fluoranthenes, involving Miura's intermolecular C-H arylation, nonaflation, and intramolecular C-H arylation, has been developed. Various 1-naphthols and haloarenes were successfully used as substrates. Reaction conditions that afford high site selectivity have been developed for the intramolecular C-H arylation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
(61 reference statements)
0
29
0
Order By: Relevance
“…A c c e p t e d m a n u s c r i p t In 2016, Manabe and co-workers described a three-steps synthetic method for the preparation of fluoranthenes, involving Miura's intermolecular C−H bond arylation, nonaflation, and 5membered ring intramolecular C−H bond cyclization (Scheme 11). 33 In order to introduce an aryl group at the C8 position of 1-naphthols, they employed the conditions described by Miura for the C−H bond arylation of with halobenzenes, 34 i.e., 2.5 mol% of Pd(OAc)2 as catalyst and Cs2CO3 as base in DMF at 110 ºC. For less reactive aryl bromides, they employed PdCl2(PCy3)2 as catalyst.…”
Section: %mentioning
confidence: 99%
“…A c c e p t e d m a n u s c r i p t In 2016, Manabe and co-workers described a three-steps synthetic method for the preparation of fluoranthenes, involving Miura's intermolecular C−H bond arylation, nonaflation, and 5membered ring intramolecular C−H bond cyclization (Scheme 11). 33 In order to introduce an aryl group at the C8 position of 1-naphthols, they employed the conditions described by Miura for the C−H bond arylation of with halobenzenes, 34 i.e., 2.5 mol% of Pd(OAc)2 as catalyst and Cs2CO3 as base in DMF at 110 ºC. For less reactive aryl bromides, they employed PdCl2(PCy3)2 as catalyst.…”
Section: %mentioning
confidence: 99%
“…Since this work, naphthols have been used by different groups to functionalize the C8‐position. In 2016, Manabe's team combined palladium catalyzed C8‐arylation of naphthols with an intra‐molecular C−H arylation to obtain fluoranthenes 6 in three steps which constitutes a fast method for the synthesis of polycyclic aromatic hydrocarbons (Scheme ) . Very recently, Spiewak and Weix reported a similar arylation reaction using a Ru(II) catalyst which allowed the introduction of heteroaryl groups …”
Section: C8‐functionalization Of Naphthalene Derivativesmentioning
confidence: 99%
“…9 More recently, Manabe and co-workers developed an elegant Pd-catalyzed method that enables the three-step synthesis of fluoranthenes via inter- and intramolecular C–H arylation reactions. 10 During the course of our studies on 1,8-diarylnaphthalenes, we have observed that monoaryl as well as symmetrical and unsymmetrical diarylnaphthalenes could be obtained selectively via Suzuki–Miyaura reaction using a tetrakis(triphenylphosphine)palladium (0) (Pd(PPh 3 ) 4 ) catalyst starting from 1,8-diiodonaphthalene ( 5 ). On the other hand, using a more active Pd catalyst, Pd(dppf)Cl 2 led to the formation of significant amounts of fluoranthene side products, which prompted us to investigate this transformation in detail.…”
Section: Introductionmentioning
confidence: 99%